Changes in neural activation underlying attention processing of emotional stimuli following treatment with positive search training in anxious children. (April 2018) - Waters, Allison M.; Cao, Yuan; Kershaw, Rachel; Kerbler, Georg M.; Shum, David H.K.; Zimmer-Gembeck, Melanie J.; Craske, Michelle G.; Bradley, Brendan P.; Mogg, Karin; Pine, Daniel S.; Cunnington, Ross
Highlights: Assessed neural correlates of treatment outcome following positive search training. Found pre- to post-treatment reductions in anxiety symptoms and neural reactivity to emotional faces within a broad neural network. Neural reactivity to the threat-bias contrast reduced from pre- to post-treatment in the mid/posterior cingulate cortex. Abstract: Prior research indicates that positive search training (PST) may be a promising home-based computerised treatment for childhood anxiety disorders. It explicitly trains anxious individuals in adaptive, goal-directed attention-search strategies to search for positive and calm information and ignore goal-irrelevant negative cues. Although PST reduces anxiety symptoms, its neural effects are unknown. The main aim of this study was to examine changes in neural activation associated with changes in attention processing of positive and negative stimuli from pre- to post-treatment with PST in children with anxiety disorders. Children's neural activation was assessed with functional magnetic resonance imaging ( f MRI) during a visual-probe task indexing attention allocation to threat-neutral and positive-neutral pairs. Results showed pre- to post-treatment reductions in anxiety symptoms and neural reactivity to emotional faces (angry and happy faces, relative to neutral faces) within a broad neural network linking frontal, temporal, parietal and occipital regions. Changes in neural reactivity were highly inter-correlated across regions. Neural reactivity to the threat-bias contrast reduced from pre- to post-treatment in the mid/posterior cingulate cortex. Results are considered in relation to prior research linking anxiety disorders and treatment effects with functioning of a broad limbic-cortical network involved in emotion reactivity and regulation, and integrative functions linking emotion, memory, sensory and motor processes and attention control.